Multiple drivers behind mislabeling of fish from artisanal fisheries in La Paz, Mexico - Munguia-Vega,Adrian; Weaver,Amy Hudson; Domínguez-Contreras,José F.; Peckham,Hoyt (PeerJ, 2021)
Seafood mislabeling has the potential to mask changes in the supply of species due to overfishing, while also preventing consumers from making informed choices about the origin, quality and sustainability of their food. Thus, there is a need to understand mislabeling and analyze the potential causes behind it to propose solutions. We conducted a COI DNA barcoding study in La Paz, Baja California Sur, Mexico, with 74 samples from fish markets and 50 samples from restaurants. We identified 38 species sold under 19 commercial names, from which at least ∼80% came from local small-scale fisheries. Overall, 49 samples, representing 40% (95% CI [31.4–48.3]) were considered mislabeled in our samples. Based on analyses where species were assigned to three price categories, economic incentives were associated with approximately half of the mislabeling events observed, suggesting that other motivating factors might simultaneously be at play. Using a network approach to describe both mislabeling (when species are mislabeled as the focal species) and substitution (when the focal species is used as substitute for others), we calculated proxies for the net availability of each species in the market. We found that local fish landings were a significant predictor of the net availability of the 10 most important commercial species at retail, but this true availability was masked to the eyes of the final consumer by both mislabeling and substitution. We hypothesize that the level of supply of each species could help explain mislabeling and substitution rates, where species in low supply and high demand could show higher mislabeling rates and rarely be used as substitutes, while species in high supply and low demand could be used as substitutes for the preferred species. Other factors affecting mislabeling include national regulations that restrict the fishing or commercialization of certain species and local and global campaigns that discourage specific patterns of consumption. We discuss how these factors might influence mislabeling and propose some solutions related to communication and education efforts to this local and global challenge.
Keywords: Seafood mislabeling; Species substitution; Small-scale fisheries; Seafood chain; Traceability; DNA barcoding